Implementation Of Online Submission Risk Based Approach (Oss-Rba) System for Business Actors in Order to Accelerate Business Licensing - Haisa, Haisa; Insan, A. Nur; Hamid, Mulyadi (Newinera Publisher, 2024)
This study aims to analyze the implementation of OSS-RBA in accelerating business licensing in Nunukan Regency and identify supporting and inhibiting factors in its implementation. This study uses a qualitative method with a descriptive approach, where data is collected through interviews with officials of the Investment and One-Stop Integrated Service Office (DPMPTSP) and business actors in Nunukan Regency. The results of the study indicate that OSS-RBA has provided convenience in business licensing through process digitization, reduced bureaucracy, and system integration with various related agencies. The main supporting factors for the implementation of OSS-RBA include regulatory readiness, HR support at DPMPTSP, and ease of online system access. However, there are still obstacles in its implementation, such as limited understanding of business actors regarding the OSS-RBA system, limited internet network infrastructure in several areas, and the complexity of requirements for businesses with medium and high risk levels. To increase the effectiveness of OSS-RBA, efforts are needed to socialize and train business actors, improve technology infrastructure, optimize assistance services, and improve coordination between agencies. With these steps, OSS-RBA is expected to be more optimal in accelerating the business licensing process and encouraging economic growth in Nunukan Regency.